Pengaruh Kompensasi dan Stres Kerja Terhadap Kinerja Pegawai pada Kantor Dinas Pekerjaan Umum Kabupaten Pasaman - Riri Mayliza; Oki Saputra (JURNAL RISET MANAJEMEN (JURMA), 2024)
Human resources are one of the supporting elements of an organization, which can be interpreted as humans who work as humans who work within an organization, as a driving force in achieving its goals. Humans who have competence are assets and function as vital non-material capital in the organization. There are two reasons why human resources influence the efficiency and effectiveness of organizations, designing and producing goods and services, monitoring quality, marketing products, allocating financial resources and determining all organizational goals and strategies. This research uses quantitative analysis using the SPSS program. Based on the results of testing the first hypothesis, it was found that the compensation variable had a positive and significant effect on employee performance at the Pasaman Regency Public Works Office. So in this research the first hypothesis (H1) is accepted. Based on the results of testing the second hypothesis (H2), it was found that the work stress variable had a positive and significant effect on employee performance at the Pasaman Regency Public Works Office. So, in this research the second hypothesis (H2) is accepted. Compensation (X1) has a positive and significant effect on employee performance at the Pasaman Regency Public Works Office, so the conclusion is that the first hypothesis is accepted. Job stress (X2) has a positive and significant effect on employee performance at the Pasaman Regency Public Works Office, so the conclusion is that the second hypothesis is accepted.